The effect of consciousness-raising tasks on the use of subject-verb agreement: a case study / Mohd Sirhajwan Idek - Idek, Mohd Sirhajwan (2014)
Subject-verb agreement (SVA) is one of the fundamental elements of English language structures. The aim of this study was to investigate the effect of consciousness-raising tasks on the use of SVA through two types of consciousness-raising (CR) tasks: Sentence Production (SP) and Grammaticality Judgment (GJ). The study involved an intact class of 28 Form 2 ESL students from a secondary school in Sabah, Malaysia. The subjects were divided into two groups. Group 1 was assigned with Sentence Production (SP) tasks and Group 2 received Grammaticality Judgment (GJ) tasks. Data was collected using a four-pronged approach which involved a pre and post-tests, interviews, questionnaire and response sheets. Learners were given a pre-test before the treatment and a post-test after the treatment to investigate their use of SVA. After an eight week treatment, the students were asked to answer questionnaires and 10 of them were interviewed. Responses sheets were also administered to the students after every CR task. The quantitative data was analyzed using descriptive statistics while the qualitative data was deductively and inductively analyzed to answer the research questions posed in the study The findings showed the SP and GJ tasks promoted SVA learning among students. The findings also revealed three challenges in learning SVA through CR tasks: inadequate hypothesis formation, emphasis of meaning over structures, and complexity of SVA. It is also discovered that CR tasks helped learners to learn SVA through cognitive domain of learning, operational skills, explicit instruction, task factors, peer collaboration and prominence of SVA. The findings indicate the importance of applying CR in ESL grammar lessons. Therefore, it can be deduced that CR tasks are effective in promoting learners’ accurate use of SVA. Henceforth teachers should look into the use of CR tasks to enhance their acquisition of SVA in the ESL classroom.